2022
DOI: 10.1037/ser0000522
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of telepsychology with veterans: A meta-analysis of services delivered by videoconference and phone.

Abstract: Veterans face a variety of stressors due to their military service and are more likely to develop psychological problems as a result. Research suggests that as many as half of veterans with mental health conditions go untreated due to barriers including lack of accessibility to services and stigma. The present study builds on previous research by using meta-analytic techniques to determine the effectiveness of telepsychologydelivered therapy with veterans. Empirical studies were included if they reported veter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 25 publications
2
33
0
1
Order By: Relevance
“…Indeed, given that telehealth was being used for MH care well before the onset of the COVID-19 pandemic, there is a strong body of evidence demonstrating that video care is noninferior to in-person MH services, 22 , 23 , 24 as well as an emerging literature suggesting that phone care may sometimes be inferior in quality to video care. 7 , 25 , 26 Findings from this survey suggest that clinician and perhaps leadership decision-making has been influenced by these data. There is less literature regarding telehealth effectiveness in PC and SC, but publication of high-quality studies has increased since the start of the pandemic 27 ; this work will be critical in informing PC and SC clinicians’ and leadership’s decision-making regarding the choice of care modalities.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, given that telehealth was being used for MH care well before the onset of the COVID-19 pandemic, there is a strong body of evidence demonstrating that video care is noninferior to in-person MH services, 22 , 23 , 24 as well as an emerging literature suggesting that phone care may sometimes be inferior in quality to video care. 7 , 25 , 26 Findings from this survey suggest that clinician and perhaps leadership decision-making has been influenced by these data. There is less literature regarding telehealth effectiveness in PC and SC, but publication of high-quality studies has increased since the start of the pandemic 27 ; this work will be critical in informing PC and SC clinicians’ and leadership’s decision-making regarding the choice of care modalities.…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, clinicians reported greater intention to continue using video services over telephone services. These findings suggest that the perceived utility of technologies varies in AMH care [ 25 ], and the merits of and attitudes toward each require consideration when integrating them into routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…The literature offers comparisons of telepsychology (either telephone or video) [ 13 , 24 ] to in-person services, but few comparisons between telepsychology modalities. One meta-analysis indicated that videoconferencing was more effective than telephone for depression and posttraumatic stress disorder in veterans [ 25 ], yet a comparison between telepsychology modalities is a major gap in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis that included 2,648 veterans previously reported similar effectiveness in treatment outcomes using both telehealth (video-conferencing and telephone) and in-person psychotherapies. Participants in the meta-analysis had a variety of mental health conditions, mostly trauma, depression, and anxiety (McClellan et al, 2021). Another meta-analysis examined the effectiveness of video-conferencing in the delivery of mental health services.…”
Section: Introductionmentioning
confidence: 99%